2023
DOI: 10.3389/fpsyg.2023.1214928
|View full text |Cite
|
Sign up to set email alerts
|

Polish version of the Aesthetic Experience Questionnaire: validation and psychometric characteristics

Agata Hiacynta Świątek,
Małgorzata Szcześniak,
Karolina Wojtkowiak
et al.

Abstract: IntroductionThe purpose of the article is to present the results of works on the Polish version of the Aesthetic Experience Questionnaire (AEQ). The AEQ is a 22-item tool for assessing aesthetic experience in the following dimensions: emotional, cultural, perceptual, understanding, and two dimensions about flow (proximal conditions and flow experience).MethodsIn the course of works on the Polish version of the AEQ, 3 independent studies with the participation of more than 800 people were carried out. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Example items: “I see the work of art as an extension of its time period," and “I lose track of time when I view the work of art." The Polish validation of the tool was used in this study [ 74 ]. Reliability indicators in the present study were as follow: perceptual–α = 0.84, emotional–α = 0.86, cultural–α = 0.83, understanding–α = 0.80, proximal conditions for flow–α = 0.79, flow experience–α = 0.87, and total score–α = 0.94.…”
Section: Methodsmentioning
confidence: 99%
“…Example items: “I see the work of art as an extension of its time period," and “I lose track of time when I view the work of art." The Polish validation of the tool was used in this study [ 74 ]. Reliability indicators in the present study were as follow: perceptual–α = 0.84, emotional–α = 0.86, cultural–α = 0.83, understanding–α = 0.80, proximal conditions for flow–α = 0.79, flow experience–α = 0.87, and total score–α = 0.94.…”
Section: Methodsmentioning
confidence: 99%
“…Susceptibility to aesthetic experiences (and their intensity) would, therefore, be a component, not a full manifestation of AQ. The authors would like to mention that the degree of convergent validity of the two concepts puzzled us during a broader study aimed at adapting the Aesthetic Experience Questionnaire 28 to Polish cultural conditions. We expected high correlations between aesthetic experiences and aesthetic competence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In research on the construction of the Aesthetic Experience Questionnaire, Wanzer and her team 8 verified the correlations between aesthetic experiences and measures of openness to experience, inspiration, curiosity, and exploration. Further, the research on the Polish adaptation of this scale revealed that “[t]he inclination for analytical observation of reality may encourage greater engagement in contemplation of art” 28 , p. 04 , as aesthetic experience is correlated with need for cognition. Therefore, the following hypothesis was formed:…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Other research has shown that people who score high on the Aesthetic Experience Questionnaire are not only more aesthetically competent, but also more cognitively inclined and more likely to turn to artistic creation and music to manage their emotions. 24 Suwiński 25 writes that the experience of beauty is a fundamental aspect of human existence, which manifests itself in cognitive processes as either pleasure or preference.…”
Section: Introductionmentioning
confidence: 99%